al-Andalus in motion : travelling concepts and cross-cultural contexts - Scott, Rachel (Rachel Jennifer); Vakil, AbdoolKarim; Weiss, Julian (King's College London medieval studies ;, 2021)
At a time when the discourse of a clash of civilisations has been re-grounded anew in scaremongering and dog-whistle politics over a Hispanic 'challenge' to America and a Muslim 'challenge' to European societies, and in the context of the War on Terror and migration panics, evocations of al-Andalus - medieval Iberia under Islamic rule - have gained new and hotly polemic topicality, championed and contested as either exemplary models or hoodwinking myths. The essays in this volume explore how al-Andalus has been transformed into a 'travelling concept': that is, a place in time that has transcended its original geographic and historical location to become a figure of thought with global reach. They show how Iberia's medieval past, where Islam, Judaism and Christianity co-existed in complex, paradoxical and productive ways, has offered individuals and communities in multiple periods and places a means of engaging critically and imaginatively with questions of religious pluralism, orientalism and colonialism, exile and migration, intercultural contact and national identity. Travelling in their turn from the medieval to the contemporary world, across Asia, Africa, Europe and the Americas, and covering literary, cultural and political studies, critical Muslim and Jewish studies, they illustrate the contemporary significance of the Middle Ages as a site for collaborative interdisciplinary thinking.